Vocal Fold Cyst Formation after Photoangiolytic KTP Laser Treatment of Early Glottic Cancer. (April 2022) - Yan, Kenneth; Friedman, Aaron D.
Objective: The incidence of post-operative glottic cyst (POGC) formation in patients treated with transoral laser microsurgery with potassium-titanyl-phosphate laser (TLM-KTP) photoablation of early glottic carcinoma (EGC) has not previously been described. Methods: A retrospective chart review was performed to identify all patients with early glottic cancer who underwent with single-modality TLM-KTP at our institution. Each patient received regular follow up with videostroboscopy for tumor surveillance. New glottic cysts seen on surveillance examinations were noted and their management was documented. Results: A total of 33 patients met inclusion criteria. Eight patients (24%) developed POGC's within the original geographic perimeter of the cancerous vocal fold(s): 6 in the infraglottic region and 2 near the vocal process, at an average of 8 months after their initial cancer surgery. Of these 8 POGC's, 7 were at the periphery of the original tumor distribution and 1 was in the center of it. No POGC's were associated with any change in voice. Four of the 8 POGC's were phonosurgically excised, all without evidence of malignancy on pathology. The remaining 4 were monitored: 2 were stable for an average of 49 months of follow up; the remaining 2 resolved spontaneously by 7 and 31 months after first identification. Conclusions: POGC's are a frequent sequela of TLM-KTP for EGC. While these results suggest that they are unlikely to represent submucosal recurrences, surgeons should have a low threshold to biopsy if there is clinical concern for such and should counsel patients pre-operatively about the potential for their formation.